DSM-5-TR: Salient Changes. (January 2023) - Bradley, Loretta; Noble, Nicole; Hendricks, Bret
The Diagnostic and Statistical Manual of Mental Disorders (DSM) is considered the authority for mental health diagnosis. Further, it is highly respected by counselors and especially by couple and family counselors as well as insurance companies. The DSM was initially published in 1952. Since its original publication 70 years ago, the DSM has experienced seven revisions with the most recent revision, the DSM-5-TR, occurring in March 2022. The focus of this article is to help couple and family counselors not only be aware of the changes but more importantly, the focus is directed toward helping them understand the changes.